Frailty as a predictor of delayed initiation of adjuvant chemotherapy in patients with ovarian cancer. Issue 1 (24th November 2022) - Ramos, Sebastian Z; Kulkarni, Amita; Oliver, Matthew; Danilack, Valery A; Mathews, Cara
Abstract : Objective: This study aimed to identify whether frailty is associated with the time between surgery and the initiation of chemotherapy for patients with ovarian cancer. Methods: This retrospective cohort study included patients 18 years or older with stage II to IV ovarian cancer who underwent primary debulking surgery at a tertiary medical center between July 2006 and July 2015. Basic demographics and clinical information were obtained from a departmental database and the electronic medical record. The Modified Frailty Index (mFI) was calculated based on 10 comorbidities and functional status yielding 11 items total. Patients were categorized by a total score: 0–1=no frailty, 2=moderate frailty and 3+=high frailty. Results: Among 451 patients, 359 had mFI scores of 0–1, 60 had a score of 2, and 32 had scores of 3+. Mean time from surgery to initiation of chemotherapy was 37 days. Mean number of days between surgery and initiation of chemotherapy increased with increasing frailty score: 36 days for the not frail group, 39 days for the moderate frailty group, and 54 days for the high frailty group (p<0.001). Time to initiation of chemotherapy of 42 days or more occurred in 23% of the no frailty group, 28% in the moderate frailty group, and 63% in the high frailty group (p<0.001). Overall survival decreased with increasing frailty scores. Conclusion: High mFI scores lead to a greater delay between surgery and chemotherapy initiation. Being able to predict delays in initiation of chemotherapy may allow oncologists to consider neoadjuvant chemotherapy, pre-habilitation before surgery, and improved preoperative counseling in high-risk patients.